School-Based Health Education as A Promotive Strategy for Preventing HIV Transmission Among Adolescents in Depok City - Sudirman Efendi; Syaiful Syaiful; Erika Emnina Sembiring; Lusia Henny Mariati; La Rakhmat Wabula (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Adolescents represent a population that is particularly vulnerable to human immunodeficiency virus (HIV) transmission due to limited knowledge, engagement in risk behaviors, and the persistence of HIV-related stigma. School-based health education serves as an important promotive and preventive strategy in efforts to reduce HIV transmission among adolescents. This community service activity aimed to enhance adolescents’ knowledge of HIV and its prevention through health education. The program was implemented at SMK YAPPA Depok using a school-based health education approach, incorporating interactive counseling, group discussions, and evaluation through pretest and posttest assessments. The target participants consisted of 175 twelfth-grade students. The educational content covered the basic concepts of HIV, modes of transmission, risk factors, and HIV prevention strategies relevant to adolescents. The results demonstrated a significant improvement in adolescents’ knowledge levels, with the proportion of students categorized as having high knowledge increasing from 10.86% before the intervention to 93.14% after the health education program. The activity also received positive responses and active participation from the participants throughout the educational process. It is expected that this community service program can serve as a model for school-based health education in HIV prevention among adolescents and further strengthen the role of nurses as health educators within the context of community nursing. Keywords: Adolescents, Community Service, HIV, Health Education, Transmission Prevention.